(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the implementation of legal protection for women victims of domestic violence and examine the Islamic legal perspective on such acts based on the Central Jakarta District Court Decision Number 180/Pid.Sus/2023/PN Jkt.Pst. The method used is normative juridical research with a statutory regulatory approach, a conceptual approach, and an Islamic normative approach. The results of the study indicate that the panel of judges has applied the provisions of Article 44 paragraph (1) and Article 45 paragraph (2) of Law Number 23 of 2004 concerning the Elimination of Domestic Violence appropriately, by declaring the defendant proven to have committed physical and psychological violence within the household. Legal protection for victims is reflected through the recognition of the victim’s rights, examination of evidence, including a post-mortem examination (visum et repertum), and legal considerations that pay attention to justice and legal certainty. From an Islamic legal perspective, domestic violence is considered contrary to the principles of compassion, justice, and protection of family members. This finding implies the importance of law enforcement that is sensitive to victims and strengthening the values ​​of justice and humanity in the national legal system